The effects of training with unstable surfaces on the strength and inter-limb asymmetry values in young soccer players - Sannicandro, I. (Medicina dello Sport, 2022)
BACKGROUND The inter-limb asymmetry refers to the strength performance of one limb with respect to the other. It differs from muscular imbalances, which represent an alteration in the strength relationship between agonist and antagonistic muscle pairs. This asymmetry seems to significantly affect performance but above all it seems to represent an injury risk factor. The study aims to analyse and understand the inter-limb asymmetry values in the young soccer players. The study also verifies whether neuromuscular training on unstable surfaces provides an effective plan able to reduce functional asymmetries and allows the strength performance increase.